2020
DOI: 10.1038/s41598-020-58894-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of Wischnewski spot development on gastric mucosa in fatal hypothermia: an experimental study in rats

Abstract: and the abundance of the HKα and HKβ proteins also increased after incubation at 32 °C for 6 h (Fig. 5B and Supplementary Fig. S2). In the gastric mucosa, the H + ,K +-ATPase pumps are expressed specifically in parietal cells and are therefore used as markers for this cell type. Immunohistochemistry showed that the expression of these proteins increased in the parietal cells on the luminal side (Fig. 5C,D).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The literature review led to the selection of 23 papers, published over the period 2001–2021 [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The review included 12 case reports, 4 retrospective analyses, 3 experimental models, 2 immunohistochemical analyses, 1 review, 1 commentary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review led to the selection of 23 papers, published over the period 2001–2021 [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The review included 12 case reports, 4 retrospective analyses, 3 experimental models, 2 immunohistochemical analyses, 1 review, 1 commentary.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Yang et al hypothesized a role of hypothermia in the stimulation of acid secretion associated with WS [ 8 ]. The authors compared rat gastric tissues kept in culture at low temperatures with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, higher average annual temperature is negatively associated with H. pylori infection and the incidence of peptic ulcer in cold climate is significantly higher than in hot climates (Yuan et al, 2015;Lu et al, 2018). This might be due to the higher gastric acid secretions in response to the cold exposures (Yang et al, 2020). Experiments on the organotypic stomach slice cultures of mice showed that the cold-stress has the potential to induce gastrin expression and enhance the gastric acid secretion (Yang et al, 2020).…”
Section: Climatementioning
confidence: 99%
“…This might be due to the higher gastric acid secretions in response to the cold exposures (Yang et al, 2020). Experiments on the organotypic stomach slice cultures of mice showed that the cold-stress has the potential to induce gastrin expression and enhance the gastric acid secretion (Yang et al, 2020). Furthermore, the diversity of food habits in hot and in cold climatic regions may also contribute to the observed variations in the prevalence of H. pylori infection and the prevalence of gastric diseases (discussed later under the heading, Diet).…”
Section: Climatementioning
confidence: 99%
“…Diagnosis of fatal hypothermia is carried out based on a combination of several common findings, such as the difference in colour between blood from the right and left ventricles, Wischnewski’s spot, haemorrhage of iliopsoas muscle and so on, which are often observed in corpses exposed to cold 1 4 . However, these findings are also observed in other pathologies such as carbon monoxide poisoning, hydrocyanic acid poisoning, and stress 5 7 .…”
Section: Introductionmentioning
confidence: 99%